La ville du futur et ses spectres. Le cas d’Eko Atlantic City à Lagos - Hervé Roquet (EchoGéo)
Futuristic imaginaries play a key role in the production of urban space. In this article, I start with the dual apparatus of virtual reality and augmented reality from the new city megaproject ‘Eko Atlantic City’ in Lagos, Nigeria, to discuss how it performs the futurity of the development project by making it tangible. I analyze how this performativity comes to ‘haunt’ the present through technological systems that go beyond the representational regime, and I introduce the concept of ‘inverted spectrality’ to describe this phenomenon. Drawing on ethnographic and visual data from a co-production of immersive videos in Lagos with people who were displaced by the construction of Eko Atlantic City, this article discusses the possibility and usefulness of creating immersive memorial counter-apparatus to resist the erasure produced by the dominant narrative of the megaproject’s promoters.